#Жилье2030 Повышение ценовой доступности жилья в регионе ЕЭК ООН - United Nations Economic Commission for Europe (United Nations, 2023)
The study explores housing affordability challenges and existing policy instruments for improving housing affordability in the regions covered by UNECE and presents examples of